Long‐Term Stability Evaluation of 0.5‐7.0 nmol/mol Dimethyl Sulfide Primary Standard Gas Mixtures by Comparison with Traceable Dynamically Diluted Gas Mixtures - Kim, Mi Eon; Kang, Ji Hwan; Kim, Yong Doo; Lee, Dong Soo; Lee, Sangil (Bulletin of the Korean Chemical Society, 2018)
Dimethyl sulfide (DMS) is a crucial precursor in the formation of aerosols that play important roles in climate change. Stable and traceable primary standard gas mixtures (PSMs) are critical for accurate measurement of the trace amounts of reactive DMS reported at sub‐nanomole per mole (nmol/mol) levels at remote monitoring sites. However, the preparation of DMS at ambient levels in high‐pressure cylinders is challenging because of its instability. This study examined the long‐term stability of 0.5–7.0 nmol/mol DMS PSMs prepared in specially treated cylinders. Ten months after the PSM preparation, the DMS PSMs were compared with traceable dynamically diluted gas mixtures (DDMs). The DMS PSMs at 2–7 nmol/mol levels were stable for 10 months with uncertainties of less than 2.5% (k = 2). However, the amount‐of‐substance fraction (i.e., mole fraction) of the DMS PSM at 0.5 nmol/mol was 5.4% less than the gravimetrically determined mole fraction, which exceeds the uncertainty of 3.5%. These findings indicate that DMS PSMs at 2–7 nmol/mol levels are sufficiently stable for use as primary standards for long‐term monitoring of trace‐level DMS in remote areas, whereas DMS PSM at 0.5 nmol/mol is not sufficiently stable.